2011
DOI: 10.1051/0004-6361/201117397
|View full text |Cite
|
Sign up to set email alerts
|

Aλ= 1.3 mm and 2 mm molecular line survey towards M 82

Abstract: Aims. We study the chemical complexity towards the central parts of the starburst galaxy M 82, and investigate the role of certain molecules as tracers of the physical processes in the galaxy circumnuclear region. Methods. We carried out a spectral line survey with the IRAM-30 m telescope towards the northeastern molecular lobe of M 82. It covers the frequency range between 129.8 GHz and 175.0 GHz in the 2 mm atmospheric window, and between 241.0 GHz and 260.0 GHz in the 1.3 mm atmospheric window. Results. Six… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
128
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 86 publications
(140 citation statements)
references
References 120 publications
12
128
0
Order By: Relevance
“…Millimeter/submillimeter (mm/submm) spectroscopic diagnostics are particularly important because intense starbursts are often deeply dust-enshrouded, especially in their early phase where limited information is available at other wavelengths. Previous mm/submm spectral scans of local starburst galaxies (e.g., Martín et al 2006;Aladro et al 2011;Martín et al 2011;Costagliola et al 2015) have demonstrated the richness of the molecular emission lines. Spatially resolved spectral line surveys are performed toward a limited number of representative galaxies such as NGC 253 (Meier et al 2015), NGC 1068 (Takano et al 2014;Nakajima et al 2015), NGC 1097 (Martín et al 2015), IC 342 (Meier & Turner 2005), and Maffei 2 (Meier & Turner 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Millimeter/submillimeter (mm/submm) spectroscopic diagnostics are particularly important because intense starbursts are often deeply dust-enshrouded, especially in their early phase where limited information is available at other wavelengths. Previous mm/submm spectral scans of local starburst galaxies (e.g., Martín et al 2006;Aladro et al 2011;Martín et al 2011;Costagliola et al 2015) have demonstrated the richness of the molecular emission lines. Spatially resolved spectral line surveys are performed toward a limited number of representative galaxies such as NGC 253 (Meier et al 2015), NGC 1068 (Takano et al 2014;Nakajima et al 2015), NGC 1097 (Martín et al 2015), IC 342 (Meier & Turner 2005), and Maffei 2 (Meier & Turner 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Most of the deep and/or unbiased chemical studies in galaxies have been carried out at very low resolution (i.e., 100 pc, Wang et al 2004;Martín et al 2006Martín et al , 2011Aladro et al 2011aAladro et al , 2013Davis et al 2013;Watanabe et al 2014) but for absorption studies toward bright continuum high-z sources where, though extremely prolific in molecular detection, no spatial information can be obtained (Muller et al 2011(Muller et al , 2014. High resolution studies toward extragalactic sources have mostly focused toward the brightest nearby galaxies, as well as on the brightest species after carbon monoxide: HCN and HCO + (NGC 253 at 3 resolution, Knudsen et al (2007); M51 at 4 , Schinnerer et al 2010; NGC 1068 at 1 , Krips et al 2011; NGC 1097 at 3 , Hsieh et al 2012; or a sample of luminous infrarred galaxies (LIRGs) at 2 −10 , Imanishi et al 2007Imanishi et al , 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Yun et al (1994) and Chynoweth et al (2008) found a large amount of H  filling the whole group as well as three distinct spurs, which connect the main galaxies of the group: M 81, M 82, and NGC 3077. Additionally, M 82 is well known for its large fraction of molecular gas in the central region (Aladro et al 2011;Naylor et al 2010). Observations by Greaves et al (2000) show a giant magnetic molecular bubble that was possibly blown out by the superwind.…”
Section: Introductionmentioning
confidence: 99%